TRANSFORMASI PEMAKNAAN PANDANGAN MASYARAKAT ETNIS BATAK SIMALUNGUN TERHADAP PEMAKAIAN BULANG - Ezra Sipayung, Dear; Ulfa Siagian, Bethesda; Sinaga, Masdiwati; Hartati Sinaga, Sri; Fitri Anggita, Adelia; Siallagan, Lasenna (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Indonesia is a developing country with diverse customs, traditions, and ancestral heritage. One of the ethnic groups in Indonesia is the Simalungun Batak ethnicity, which has distinctive characteristics compared to other ethnicities, one of which is its traditional clothing called Bulang. This research aims to analyze the transformation of the use of Bulang in the Simalungun Batak ethnicity. This study uses a qualitative method, seeking to explain the transformation of the meaning of Bulang's use through descriptive analysis. Data collection was conducted by direct interviews with several members of the Simalungun Batak community. The results show that Bulang is traditionally worn by women who are married or have become wives.